Investigating the Anticancer Potential of Salvicine as a Modulator of Topoisomerase II and ROS Signaling Cascade - Dey, Dipta; Hasan, Mohammad Mehedi; Biswas, Partha; Papadakos, Stavros P.; Rayan, Rehab A.; Tasnim, Sabiha; Bilal, Muhammad; Islam, Mohammod Johirul; Arshe, Farzana Alam; Arshad, Efat Muhammad; Farzana, Maisha; Rahaman, Tanjim Ishraq; et al. (Frontiers in Oncology, 2022)
Salvicine is a new diterpenoid quinone substance from a natural source, specifically in a Chinese herb. It has powerful growth-controlling abilities against a broad range of human cancer cells in both in vitro and in vivo environments. A significant inhibitory effect of salvicine on multidrug-resistant (MDR) cells has also been discovered. Several research studies have examined the activities of salvicine on topoisomerase II (Topo II) by inducing reactive oxygen species (ROS) signaling. As opposed to the well-known Topo II toxin etoposide, salvicine mostly decreases the catalytic activity with a negligible DNA breakage effect, as revealed by several enzymatic experiments. Interestingly, salvicine dramatically reduces lung metastatic formation in the MDA-MB-435 orthotopic lung cancer cell line. Recent investigations have established that salvicine is a new non-intercalative Topo II toxin by interacting with the ATPase domains, increasing DNA–Topo II interaction, and suppressing DNA relegation and ATP hydrolysis. In addition, investigations have revealed that salvicine-induced ROS play a critical role in the anticancer-mediated signaling pathway, involving Topo II suppression, DNA damage, overcoming multidrug resistance, and tumor cell adhesion suppression, among other things. In the current study, we demonstrate the role of salvicine in regulating the ROS signaling pathway and the DNA damage response (DDR) in suppressing the progression of cancer cells. We depict the mechanism of action of salvicine in suppressing the DNA–Topo II complex through ROS induction along with a brief discussion of the anticancer perspective of salvicine.